Managing Complexity - Mariotti, Humberto (2014)
This article is a brief introduction to complexity, complex thinking and complexitymanagement. Its purpose is to present an update on the applications of the complexitysciences particularly to the universe of corporations and management. It includes anexample taken from the globalized world and two more stories from the corporateenvironment. Some details on how to think about complexity and how to apply theconceptual and operative tools of complex thinking are provided. The article ends withsome remarks on personal, interpersonal and corporate benefits of the complexthinking.